The Fallout from the Financial Crisis (1) Emerging Markets under Stress - Reisen, Helmut (OECD Development Centre Policy Insights, 2008)
The contagion of the global credit crisis from the industrialised countries to the emerging markets has taken some time to develop. Then, in October 2008, it spread rapidly, afflicting all emerging markets, without any distinction or regard to their so-called "fundamentals". For believers in "decoupling", the high growth rates, massive foreign exchange (FX) reserves, balanced budgets and rising consumerism in the emerging markets at first reassured investors. It is now clear that the diagnosis of emerging-market policy performance suffered from hyperbole. In the end, all emerging market asset classes were hit: stocks, bonds and currencies